Index tracking and enhanced indexation using a parametric approach - Chavez Bedoya, Luis (2014)
Based on the work of Brandt et al.(2009), we formulate an index tracking and enhanced indexation model using a parametric approach. The portfolio weights are modeled as functions of assets characteristics and similarity measures of the assets with the index to track. This approach permits handling nonlinear and nonconvex objectives functions that are difficult to incorporate in existing index tracking and enhanced indexation models. Additionally, this approach gives the investor more information about the portfolio holdings since the optimization is performed over portfolio strategies. Finally, an empirical implementation and an analysis of selected characteristics are presented for the S&P500 index. DOI: http://dx.doi.org/10.1016/j.jefas.2014.03.003